2014
DOI: 10.1183/09031936.00116814
|View full text |Cite
|
Sign up to set email alerts
|

Use of forced vital capacity and forced expiratory volume in 1 second quality criteria for determining a valid test

Abstract: The 2005 American Thoracic Society (ATS)/European Respiratory Society (ERS) spirometry guidelines define valid tests as having three acceptable blows and a repeatable forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1). The aim of this study was to determine how reviewer and computer-determined ATS/ERS quality could affect population reference values for FVC and FEV1.Spirometry results from 7777 normal subjects aged 8–80 years (NHANES (National Health and Nutrition Examination Survey) III) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 13 publications
3
46
0
3
Order By: Relevance
“…2 The authors' finding that failure to satisfy end-of-test criteria was a common error is consistent with data recently published by Hankinson et al, 3 who suggested that strict adherence to end-of-test criteria may result in the unnecessary rejection of valid data. Based on these data, it seems reasonable to expect that future ATS/ERS recommendations may curtail currently used end-of-test criteria.…”
Section: To the Editorsupporting
confidence: 84%
“…2 The authors' finding that failure to satisfy end-of-test criteria was a common error is consistent with data recently published by Hankinson et al, 3 who suggested that strict adherence to end-of-test criteria may result in the unnecessary rejection of valid data. Based on these data, it seems reasonable to expect that future ATS/ERS recommendations may curtail currently used end-of-test criteria.…”
Section: To the Editorsupporting
confidence: 84%
“…These were: ‘Blank’ (ie, no error message), ‘Accept’, ‘Accept Below6sec’ (acceptable blow, with plateau, even though expiration time less than 6 s) and ‘Below6sec’ (expiration below 6 s, but no other error message in the manoeuvre). Although this deviates from the ATS/ERS guidelines, a recent publication has suggested that strict end-of-test criteria are the ones most likely to lead to rejection of satisfactory manoeuvres 12. The highest value of both FEV 1 and FVC from acceptable curves was identified.…”
Section: Methodsmentioning
confidence: 72%
“…17 Patients also completed a short questionnaire to ascertain out of pocket expenses for attendance (Appendix 3) and health status (EQ-5D). 18 Patients' height was measured to the nearest cm using a portable stadiometer (or estimated using arm-span if necessary).…”
Section: Spirometry Diagnostic Assessmentsmentioning
confidence: 99%